Mechanisms of Resistance to BCR-ABL Kinase Inhibitors - Diamond, Joana (2013)
Since the introduction of imatinib mesylate for the treatment of chronic myeloid leukaemia, impressive clinical responses were observed in the majority of patients in chronic phase. However, not all patients experience an optimal response to imatinib mesylate or even to the more potent, second generation tyrosine kinase inhibitors. Furthermore, responses are not sustained in a number of patients, and it is yet unclear whether the inhibitors can be safely discontinued in patients who achieve long-term remission. The emergence of resistance to second generation tyrosine kinase inhibitors has become a significant problem that led to extensive studies on the causal mechanisms. This review will describe our current state of knowledge on why and how chronic myeloid leukaemia cells can develop resistance to second generation tyrosine kinase inhibitors.